A note on iterated spherical average on Lebesgue spaces. (March 2019) - Fan, Dashan; Lou, Zengjian; Wang, Zijian
Abstract: For the spherical average A and the Laplace operator Δ, we study the iterated operator Δ A N and find the minimal positive integer N to ensure the L 1 R n boundedness of Δ A N . Using a constructive proof, we completely solve a question posted by Belinsky et al. (2003).